(untitled) (Bangladesh Journal of Otorhinolaryngology, 2013)
Objective: To determine amongst biomaterials (Teflon and Silicon) and autologous materials (autologous incus and cartilage), the one which give the best results of ossiculoplasty, in terms of increase in hearing sensitivity including cost effectiveness. Methods: Study was conducted in Eras Lucknow Medical College & Hospital, Lucknow, India. Randomized prospective crossover study with eighteen months follow up. 80 patients of Chronic Suppurative Otitis Media (CSOM) were randomly assigned for ossiculoplasty using biomaterials (Teflon and silicon) and autologous materials (bone and cartilage ). Surgical outcome was compared for all the four types of implant material used, in terms of increase in hearing sensitivity, extrusion rate, cost effectiveness. Pre-operatively all patients had a pure tone audiogram with a four frequency average (0.5/1/2/4 kHz) calculated for both air conduction and bone conduction. Post-operatively a pure tone audiogram using (0.5/1/2/4 kHz) was performed at 18 months follow-up. Results: Mean hearing gain (change in A-B gap) was 20.80±7.08 dB in autologous group and 19.93±7.27 dB in biomaterials. Hearing Success Rate-It indicates, total no. of patients, whose postoperative AB Gap (calculated at 500Hz,1,2,3 KHz) is equal to or less than 20 dB. In the present study the overall hearing success rate at follow up period of 4 months is 78.8%. For autologous implants it is 80% and for biomaterials it is 77.5%. Conclusion: The study concluded that there is no significant difference in improvement in AB gap, extrusion rate of implant and overall success rate between biomaterials (Teflon, silicon) and autologous implants (autologous incus, cartilage). The only significant difference between the two groups was the cost effectiveness. Hence, it is concluded in our study that the biomaterials and autologous implants used in the study have equal overall efficacy. The autologous material requires no extra cost so it can be considered as a preferred choice of implant, in comparison to biomaterial in SAARC countries, where the majority is of poor patients. DOI: http://dx.doi.org/10.3329/bjo.v19i1.12619 Bangladesh J Otorhinolaryngol 2013; 19(1): 29-35